2020
DOI: 10.1021/jacs.0c00907
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and Extrinsic Control of the pKa of Thiol Guests inside Yoctoliter Containers

Abstract: Despite decades of research, there are still many open questions surrounding the mechanisms by which enzymes catalyze reactions. Understanding all the noncovalent forces involved has the potential to allow de novo catalysis design, and as a step toward this, understanding how to control the charge state of ionizable groups represents a powerful yet straightforward approach to probing complex systems. Here we utilize supramolecular capsules assembled via the hydrophobic effect to encapsulate guests and control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 84 publications
0
18
0
Order By: Relevance
“…We have shown that bound thiol guests are more acidic inside 1 2 , by up to 2.5 p K a units (it transpires that guest motif has a much larger effect on p K a ). 41 We have also observed that rates of macrocyclization of α,ω-thio-alkane halides inside 1 2 are almost 4 orders of magnitude faster than inside 2 2 . 42 These findings also showed that the stabilization of the transition states (TS) for cyclization was greater than that of thiolate stabilization, suggesting a rather complex mechanism by which these capsules affect chemical reactivity.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…We have shown that bound thiol guests are more acidic inside 1 2 , by up to 2.5 p K a units (it transpires that guest motif has a much larger effect on p K a ). 41 We have also observed that rates of macrocyclization of α,ω-thio-alkane halides inside 1 2 are almost 4 orders of magnitude faster than inside 2 2 . 42 These findings also showed that the stabilization of the transition states (TS) for cyclization was greater than that of thiolate stabilization, suggesting a rather complex mechanism by which these capsules affect chemical reactivity.…”
Section: Introductionmentioning
confidence: 53%
“…Although it was not possible to observe the 1 H NMR signal for a −NH 2 or −NH 3 + group of the bound guest, and therefore not possible to use 1 H NMR spectroscopy to determine ammonium p K a values, we can use the previously determined p K a values for thiols within 1 2 , and 2 2 as a guide. 41 This data suggests that the p K a of a bound ammonium can range from 6 to 12; the amine would be a weak base inside 1 2 , and a relatively strong base inside 2 2 . That trace protonation of the guest inside 2 2 is a possibility that was suggested by a small change in the guest binding region of the 1 H NMR spectrum of the complex when an additional 50 equiv of NaOD was added.…”
Section: Resultsmentioning
confidence: 94%
“…. π interactions [36], and of binding modes inside relatively small (of "yoctoliter" volume) capsules [37]. In such investigations, a possibility should be considered that fairly different position(s) of the ligand might be compatible with an experimental value of the complexation shift.…”
Section: Discussionmentioning
confidence: 99%
“…[4,8,9] Meanwhile,t he supramolecular forces inherent in electrostatic interactions,h ydrogen binding,hydrophobic effect, etc., are also crucial in modulating the reactivity and selectivity of enzymes. [10][11][12][13][14] Aprominent way is to modify acidity-basicity of functional residuals or hosted substrates,w hich facilitates abstraction of proton and stabilization of favored charge-state, [15,16] paving the way for nucleophilic,e lectrophilic or acid/base enzymatic reactions intrinsic in the state of protonation. [17,18] In these regards,m uch effort has been devoted to the design and assembly of supramolecular cages with varied sizes,s hapes,c avities and active-sites for supramolecular catalysis,a ccomplishing reaction acceleration, intermediate stabilization, and special chemical selectivity on the basis of supramolecular confinement effect enforced by the cagedefined nanospace and geometry.…”
Section: Introductionmentioning
confidence: 99%